Determinación de la eficacia de extracto de propoleo (flavonoides) aplicado intrauterinamente en el puerperio en vacas de tercer parto de la hacienda Pasochoa, cantón Mejía - Uquilla Patiño, Jose Bernardo (2015)
The object of study was, "evaluate the effectiveness of the flavonoids used at three different concentrations on normal bovine postpartum time". 20 cows were selected from 4 - 6 years in post partum stage and were placed randomly in treatment. I was to the treatment administered via uterine flavonoids, 20 ml of 10% flavonoids, performing a uterine wash the product referred to 10 days post gynecological examination before delivery. Treatment II and III were similar only varying the concentration of the flavonoids being treating II: 20 ml of 25% flavonoid and treatment III: 20 ml of 45% flavonoids. The controls for data extraction was performed by ultrasonography at 15 and 21 days postpartum. Treatment II was the best performing: cervix along with an average of 5.8 cm at 21 days, 5.67 mm thick and 32.2 mm in diameter wall….